Keterkaitan Antara Kelimpahan Zooplankton dengan Fitoplankton dan Parameter Fisika-Kimia di Perairan Jailolo, Halmahera Barat - ., Yuliana (Maspari Journal : Marine Science Research, 2014)
Zooplankton have an important role in water especially in the food chain, this organism is a consumer I which plays a major role in bridging the energy transfer from primary producers (phytoplankton) to living things are at a higher trophic level (fish and shrimp). This research aimed to analyze the relationship between the abundance of zooplankton to phytoplankton and phisic-chemistry parameters at Jailolo waters, HalmaheraBarat. The research was conducted in February 2011. The observation of zooplankton were taken from 7 stations by filtration method. The result showed that there were 7 genera of 4 (four) groups: Ciliate(1 genus), Crustaceae (4 genera), Rotifera (1 genus), and Sarcodina (1 genus). Abundance of zooplankton range from 1,429 - 32,571 cell/m3, the highest on Gufasa and Tuada (32,571 cell/m3) and the lowest on Bobanehena (1,429 cell/m3). The value range of zooplankton biological index were diversity index (H ') = 0.4506 to 1.5091, equitability index (E) = 0.6356 to 0.9710, and the dominance index (D) = 0 , 2379 to .7222. There is a close relationship between the abundance of zooplankton to phytoplankton abundance and physico-chemical parameters of waters, with a coefficient of determination (R2) of 0.972 and the regression equation Y = - 7194397 - 0.0836 phytoplankton + 269630 temperature+ 6195 salinity + 140943 DO - 128086 pH.